Developing and validating a questionnaire for sensory environment: A pilot study / Roslinda Ghazali, Siti Rasidah Md Sakip and Ismail Samsuddin - Ghazali, Roslinda; Md Sakip, Siti Rasidah; Samsuddin, Ismail (2021)
Autism is a complex neurobehavioral disorder characterized by impairment in social interaction, communication, and repetitive behaviors, interests and activities. Environmental influences, such as early intervention and educational programs, have already shown to improve the quality of life for autistic. The physical learning environment also significantly improves learning outcomes for them. Therefore, architects suggested considering the learning environment to ensure that the space is convenient and comfortable for the autistic. The researchers aim to formulate the instrument for the survey that is appropriate, and the respondent understands the question better. The process to construct the questionnaire is difficult and complicated and requires verification of its usefulness before implementation. The objective is to measure instruments and analysis of their main features, reliability, and validity. The survey asked the respondents about their knowledge and awareness in their environment regarding autism. In this pilot survey 35 respondents participated. Their preference based on their knowledge and awareness regarding four-components - sensory stimulation (lighting, smell, color and visual), sensory sensitivity (sight, sound, smell, taste, touch, proprioception, vestibular), the sensory design (acoustic, compartmentation, spatial sequencing, thresholds, escape space, sensory zoning, safety, and security) and physical learning environment(accessible, wayfinding, scale, toilet accommodation, ventilation, window, quiet room, legibility, and furniture). The researcher used the Statistical Program for Social Sciences Software (SPSS) version 25 to analyze this pilot study. The questionnaire can be generalized for real data collection with this reliable and valid research instrument.